2019
DOI: 10.1111/1471-0528.15670
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcomes in pregnancies complicated by the inherited aortopathy Loeys–Dietz syndrome

Abstract: Objective Pregnancies in women with Loeys-Dietz syndrome (LDS) are rare and are typically documented in case reports only. Early reports suggested high rates of maternal complications during pregnancy and the puerperium, including aortic dissection and uterine rupture, but information on fetal outcomes was very limited.Design A retrospective cohort study.Setting Eight specialist UK centres.Sample Pregnant women with LDS.Methods Data was collated on cardiac, obstetric, and neonatal outcomes.Main outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…3) Cauldwell, et al reported 20 pregnancies in 13 women with LDS, in-cluding one woman with a history of ARR after her first pregnancy; however, no AD occurred in their cohort. 4) Including the report from Cauldwell, et al, in which precise history is unknown, there were only six cases of pregnancy in patients with LDS with a history of ARR, and four of these patients had AD after delivery. [4][5][6][7] These results indicate that patients with LDS with a history of ARR must be informed of risks prior to pregnancy, because they require special attention during pregnancy and after delivery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3) Cauldwell, et al reported 20 pregnancies in 13 women with LDS, in-cluding one woman with a history of ARR after her first pregnancy; however, no AD occurred in their cohort. 4) Including the report from Cauldwell, et al, in which precise history is unknown, there were only six cases of pregnancy in patients with LDS with a history of ARR, and four of these patients had AD after delivery. [4][5][6][7] These results indicate that patients with LDS with a history of ARR must be informed of risks prior to pregnancy, because they require special attention during pregnancy and after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we propose a management strategy for pregnant women with LDS following ARR, as shown in Table II. Women with LDS without a history of ARR seem to have favorable pregnancy outcomes; however, because fatal AD occurs in 1%-2% of these women, 3,4) we used the same protocol for each LDS pregnancy after thorough discussion with the patient. Considering the beneficial effect of lactation for both mother and newborn, lactation prevention in MFS-related diseases has been controversial; however, given the promising results observed by Habashi, et al in mice, the option to prevent lactation should be discussed with women with LDS regardless of…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from the catastrophic fetal outcomes that can result from maternal aortic dissection, fetal development does not seem to be affected. In a series of 20 pregnancies in 13 women, the rate of preterm delivery was 50%, but there were otherwise normal fetal outcomes. Suggested management guidelines in pregnancy are summarized in Table .…”
Section: Hhh Syndromementioning
confidence: 96%